Netrin-1 attenuates the progression of renal dysfunction by blocking endothelial-to-mesenchymal transition in the 5/6 nephrectomy rat model. Issue 1 (December 2016) - Bai, Jiuxu; Hao, Junfeng; Zhang, Xiaoling; Cui, Hanmin; Han, Jingming; Cao, Ning
Abstract Background Endothelial-to-mesenchymal transition (EndoMT) is a crucial event during kidney interstitial fibrosis and it is believed to be inhibited by netrin-1. Our aim was to determine the influence of netrin-1 on renal EndoMT in chronic kidney disease by studying its effect in 5/6 nephrectomized (Nx) rats. Methods Male Sprague–Dawley rats were divided into three groups (10 rats/group): sham-operated rats treated with control adenovirus; 5/6 Nx rats treated with control adenovirus; and 5/6 Nx rats treated with recombinant adenovirus expressing the netrin-1 gene (Ad-netrin-1). Rats were sacrificed 13 weeks after surgery. Blood urea nitrogen (BUN) and serum creatinine (Scr) levels were measured regularly after surgery. After the rats were sacrificed, pathological changes in renal tissues were analyzed histologically. Immunofluorescence was performed to evaluate the co-expression of CD31 and α-SMA. CD31, α-SMA and Snail mRNA were detected by RT-PCR. Protein expression was detected by western blot. Results Renal function and histopathological damage were significantly improved in Ad-netrin-1-treated 5/6 Nx rats. In the sham and control-treated 5/6 Nx rats, the percentage of CD31+ /α-SMA+ cells increased, which indicated EndoMT. However, the percentage of CD31+ /α-SMA+ cells were reduced in the netrin-1-treated 5/6 Nx rats, which indicates netrin-1-induced blocking of EndoMT. Conclusion From the results, it seems that netrin-1 attenuates the progression of renal dysfunction by inhibiting EndoMT in 5/6 Nx rats. Netrin-1 can therefore be considered as a potential therapeutic agent for the treatment of renal fibrosis.